Branding in Islamic Commercial Law – Eyeing Commercial Gains Versus Opportunities for Introducing SharÊ‘ah Legal Ethics - LUTFULLAH SAQIB; SAIRA AFZAL (Hamdard Islamicus, 2018)
According to recent research, the ×alÉl (permissible in Islamic law) food market represents 16% of the total global market, which is expected to double in the near future. A huge potential, therefore, lies in the target market of Muslim consumers. In order to penetrate the ×alÉl markets, firms are employing brand Islamization strategies as per rules of Islamic Commercial Law. Most firms, however, are doing so for extra commercial gains. In this paper an effort has been made to introduce and highlight some of the legal ethical aspects of the branding practices in Islamic law, predominantly, in Islamic commercial law. The purpose of this paper is to analyze specific commercial activities carried out in the name of brand Islamization. One of the objectives is to raise awareness that increasing aspirations related to Islamic branding are, in fact, masked activities of utilizing huge potentials that exist both for Muslim and non-Muslim firms. New methods of incorporation of Islamic legal ethics in the brand design and developmental strategies are also explored in this paper. The paper clarifies that Islamic brandingis not merely limited to the “Halal” factor but is one that is purely SharÊ‘ah (Islamic Law) compliant, both in substance and form.